A correlation study of happiness, motivation and stress from creative pursuits. - Krishna Kumar, V. (SAGE Publications, Ltd., 2023)
V. Krishna Kumar, PhD, professor emeritus, Westchester University, discusses a correlation study of happiness, motivation and stress from creative pursuits, including research design, recruitment, ethical considerations, data collection and analysis, research findings, challenges faced, and lessons learned.